ANALISIS PENINGKATAN KOMITMEN AFEKTIF DAN PRESTASI KERJA BERBASIS ETOS KERJA ISLAM DAN BUDAYA KERJA TENAGA PENDIDIK - Akhmad Mufarikhin (Jurnal Riset Bisnis Indonesia, 2015)
Hard working, or in other word is also called work ethic is a essential requirement to achievehappiness in life and hereafter, since a high work ethic produces high productivity as well. Thequality of teacher performance will determine the quality of education result or output of the graduatescore because teacher is a party with the most direct contact with students in teaching and learningprocess in educational institute. This research aims to examine the enhancement model of affectivecommitment and work achievement based on Islamic work ethics and working culture of the educatorin Yayasan Penididikan Islam Al- Falah, Jepara. This research is one kind of explanatory research,with the sample number 120 person and used PLS as data analysis tool. Based on the data analysis,it showed that if the Islamic work ethics improves, the affective commitment of human resource willalso improve. Islamic work ethics does not have significant relation with HR work achievement. Workculture does not have significant relation with the affective commitment of HR. Then, Islamic workethics does not have significant relation with work achievement.Keywords: Islamic work ethics, work culture, affective commitment, work achievement.